2(v+3)-3=15

Simple and best practice solution for 2(v+3)-3=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v+3)-3=15 equation:


Simplifying
2(v + 3) + -3 = 15

Reorder the terms:
2(3 + v) + -3 = 15
(3 * 2 + v * 2) + -3 = 15
(6 + 2v) + -3 = 15

Reorder the terms:
6 + -3 + 2v = 15

Combine like terms: 6 + -3 = 3
3 + 2v = 15

Solving
3 + 2v = 15

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2v = 15 + -3

Combine like terms: 3 + -3 = 0
0 + 2v = 15 + -3
2v = 15 + -3

Combine like terms: 15 + -3 = 12
2v = 12

Divide each side by '2'.
v = 6

Simplifying
v = 6

See similar equations:

| (12x+9)+(2x+21)=360 | | 5a(3.4b)= | | 7(2x-1)=8x-25 | | (2x+3)(9x+6)=43+2(3x+1)(3+1) | | -2.7(4y)= | | a=215.5t+2500 | | x^2+2x-2=-4x+5 | | -1.75g-8.75=3g+7.5 | | 4+4b-(2b+3)-(5b+9)= | | z-5z+7z= | | 6(x-5)-4x=3(4x-5) | | [3x+4]+7=2 | | 2(h+-2)-2=10 | | 5x^2-50x-125=0 | | x+(10-45)=84-74 | | 8=2(k+2) | | -9.1x=63.7 | | 6+6x=-4(6-3x) | | 3X^2+8X+XY-4Y=11 | | 1-4x=-7+28 | | (3x^2)+(8x)+(xy)-(4y)=11 | | (3x+8)+(2x+3)=180 | | 6(2x-3)=8x-2 | | 4(x-6)+6=6(x+2)-4 | | 0=-2x^2+4x+4 | | -c+3.4=6.21 | | -2.1m=8.4 | | 9-2x=7+2x-6 | | 10=2(y-4)+4 | | 56=c+24 | | -8(4b+3)+(33b-7)=0 | | 7x-9=3(x+5) |

Equations solver categories